PELATIHAN DASAR MENGGAMBAR TEKNIK SISWA SMK PGRI JATIBARANG - Farhan, Ahmad; Alba Pradana, Claudha; Kusmayadi, Adi; Irawan, Candra (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2024)
PGRI Jatibarang Vocational School is one of the vocational schools on Jalan Mayor Dasuki No. 159 Jatibarang, Indramayu Regency, West Java Province. Based on the results of observations on PGRI Jatibarang Vocational School students who are PKL at the Politeknik Negeri Indramayu (Polindra), there are problems regarding understanding technical drawings. In order to improve the skills of PGRI Jatibarang Vocational School students, especially in understanding technical drawing to increase the competitiveness of graduates. The PKM team conducted a group discussion forum (FGD) with vocational school stakeholders, especially vocational school students who were doing internships at the D4 Manufacturing Design Study Program. The PKM team collected data and explored the problems that existed among the intern students. After conducting the FGD, the PKM Team conducted technical drawing training for students at the PGRI Jatibarang Vocational School, Indramayu Regency. The results of this training show a fairly effective increase based on pretest and posttest scores with N-Gaing.